Reflexivity and Practice in COVID-19: Qualitative Analysis of Student Responses to Improvisation in Their Research Methods Course - Elizabeth L. Spradley (Central States Communication Association, 2021)
The improvisations needed to adapt to COVID-19 teaching and learning conditions affected students and faculty alike. This study uses chaos theory and improvisation to examine an undergraduate communication research methods course that was initially delivered synchronously/face-to-face and then transitioned to asynchronous/online in March 2020. Reflective writings were collected at the end of the semester with the 25 students enrolled in the course and follow-up interviews conducted with six students. Thematic analysis revealed that available and attentive student-participant, student-student, and student-instructor communication complemented learner-centered and person-centered goals, but unavailable or inattentive communication, especially with participants and students in the research team, contributed to negative perceptions of learner-centered goals. Implications explore how communication research methods pedagogy may achieve greater available, attentive, and learner/person-oriented goals through modeling, resourcing, reflexivity, and appreciation in online and offline course delivery to enhance shifts in communication pedagogy, whether voluntarily or involuntarily initiated by faculty.